(untitled) (Biodiversitas Journal of Biological Diversity, 2018)
Yora M, Syukur M, Sobir. 2018. Characterization of phytochemicals and yield components in various okra (Abelmoschus esculentus) genotypes. Biodiversitas 19: 2323-2328. Okra is a group of vegetable and medicinal plants possessing various health benefits. This plant has different shapes, colors and nutritional content. In Indonesia, this plant has not been widely cultivated, because the socialization and information of okra benefits to the Indonesian people are still limited. The aims of this study were to analyze phytochemicals, anthocyanins and carotene content, and to analyze the correlation among okra genotypes based on their morphological characters. This study was conducted from September 2017 to January 2018, using Complete Randomized Group Design with three replications and 13 genotypes namely PB01Nai, PB02Zah, PB03Clem, PB04Stri, PB13-293, PB05-291, PB06-004, PB07-127, PB08P1, PB09P2, PB10-MC, PB11-069, and PB12-OR. The observation was made on the variables of phythochemical, anthocyanin, carotene, chlorophyll and yield components on okra fruit. The results showed that all okra fruits have steroid phytochemical content and some of them had phytochemical content of Saponin and Tanin. Based on the carotene and chlorophyll analysis of 13 okra fruit genotypes, it showed that PB11-069 genotype contained the highest carotene and chlorophyll contents. While okra fruit having the highest anthocyanin content was PB05-291. The results of cluster analysis showed that okra was clustered into three color groups. The anthocyanin content found in okra fruit does not correlated with the yield component variable. Chlorophyll-?, ?, and total chlorophyll are positively correlated to carotene in okra fruit and variable number of fruits. The character of number and weight per plant greatly influences the determination of the selection process. Accordingly, the characters can be used as a selection character so as to produce a high yield okra containing high chlorophyll and carotene contents.